Challenges and Responsibilities of Nursing Students as Professional Citizens in Healthcare Services - Firdaus Edo Putranto; Renaka Wawang Siwijalu; Ronal Poteplaza; Ludowikus Amabel (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This paper explores the challenges and responsibilities of nursing students as professional citizens within the healthcare system. In an era marked by rapid health transitions, social inequality, and digital transformation, nursing students are expected not only to acquire clinical competence but also to demonstrate civic engagement and social accountability. Through a literature review approach, this study examines the roles of nursing students in promoting health equity, advocating for community welfare, and influencing healthcare policy. The findings reveal that nursing students face several obstacles in fulfilling their civic duties, including limited curriculum content, lack of institutional support, and academic pressures. However, when properly guided and supported, they can become key agents of change in addressing health disparities, strengthening community trust, and promoting ethical healthcare practices. The paper concludes that integrating citizenship education into nursing programs is essential for producing socially responsible healthcare professionals who are capable of responding to both individual and collective health needs. This study contributes to the broader understanding of how nursing education can be designed to prepare future nurses not only as caregivers but also as advocates, educators, and civic leaders in public health.